Financial and Enterprise Restructuring in Emerging Market Economies - Fries, Steven (IMF Working Papers; Working Paper, 1994)
This paper examines alternative approaches to building sound financial structures in emerging market economies. The foremost task is to resolve the bad loan problem and to recapitalize insolvent state banks. By restoring an incentive for banks to price accurately the risks of new lending, this effort would be an important first step in strengthening financial control. However, we argue that this endeavor is only part of the task at hand; the remainder is to provide financing that facilitates the economic restructuring of SOEs. A comprehensive strategy may involve combining discipline derived from enforcing existing loans to SOEs with adequate funding for new forms of ownership, including financing for enterprise sell-offs and leasing.